Studying The Simultaneous Effect Of Black Nanocarbon And Polyester Fibers With High Stability On Mechanical Properties Of Asphalt Mixture - Zahedi, Mohsen; Zarei, Mohammad (The Turkish Online Journal of Design Art and Communication, 2016)
Undoubtedly, making asphalt mixture with good quality has been always considered by road constructor engineers. In this research, by adding different percent amounts of black nanocarbon and polyester fibers jointly in asphalt mixture and doing Marshall tests, data analysis and drawing necessary diagrams, it was observed that adding these two additives causes the changes on Marshall Results. The results indicated that Marshall Stability of made samples with joint effect of additives in a special percent is increased to 71%. With increasing of stability, fluidity was also increased. Total volume of asphalt mixture (VTM) in most of percent amounts was increased relatively. On the other hand, special weight of asphalt mixture in all percent amounts (except a special percent) was reduced. Finally void volume of aggregates (VMA) was increased relatively and the percent of space filled with bitumen (VFA) except a special percent was reduced. By studying and analyzing the diagrams, optimum percent for combination of black nanocarbon and polyester fibers with high stability was obtained in order 15% black nanocarbon and%0.5 polyester fibers with high stability which has had the best effect on asphalt mixture. Finally, it was concluded that the obtained mixture can be used in the regions with moderate weather and heavy traffic.
Keywords: black nanocarbon; asphalt; polyester fibers; Marshall; pavement; siyah nanocarbon; asfalt; polyester elyaf; kaldırım